Serological and molecular epidemiology of contagious ecthyma among sheep and goats in Negeri Sembilan, Malaysia - Zaharaddeen, Lawan (2020)
Contagious ecthyma (CE) is a zoonotic and highly contagious epitheliotropic viral disease of goats, sheep and many species of wild ruminants. It is characterized by the development of skin lesions around mouth, lips, ears, nose, and legs. This study is aimed to determine the seroprevalence and possible risk factors associated with CE infection in sheep and goats as well as to determine genetic variation of the virus isolated from scab lesions. A total of 341 serum samples were collected from animals of five (5) different goats and sheep farms. All the farms were selected based on the approval and directive by the Department of Veterinary Services (DVS). The farms were located in Lenggeng (A), Seremban (B), Jelebu (C), Senawang (D), and Mendom (E) in Negeri Sembilan. Only farm C in Jelebu practiced intensive management system while all the remaining farms practiced semi intensive management. The distribution of the animals in relation to 341 samples collected according to the 5 farms are; farm A in Lenggeng with 102 samples (91 goats and 11 sheep), farm B in Seremban with 75 samples all goats, farm C in Jelebu with 60 samples all sheep, farm D in Senawang with 55 samples all goats and farm E in Mendom with 49 samples (36 goats and 13 sheep). In term of gender of the animals, farm A comprises 18 bucks, 73 does, 2 rams and 9 ewes. Farm B has only 31 bucks and 44 does. Farm C has only 3 rams and 57 ewes. Farm D housed 8 bucks and 47 does while farm E comprises of 11 bucks, 25 does, 2 rams and 11 ewes. In term of age of the animals, farm A has 80, 11, 8 and 3 adult goats, kids, adult sheep and lamb respectively. Farm B has only 44 adult goats and 31 kid’s contribution to this study. Farm C contributed 53 adult sheep and 7 lamb. Farm D has 48 adult goats and 7 kids while farm E contributed with 30, 6, 11 and 2 adult goats, kids, adult sheep and lambs respectively. Serum samples collected were tested for CE antibody by using of indirect ELISA and serum neutralisation test. Viral culture and molecular confirmation of CE virus was done on six (6) scabs samples obtained from mouth, ear, hooves, and thigh lesions of suspected CE infected animals. Polymerase chain reaction (PCR) was used to amplify ORFV major envelop glycoprotein (B2L) and immunodominant envelope protein (F1L) genes following extraction of the viral genomic DNA from the processed scab lesions. The virus was first isolated in lamb testicular cells (LT) and Vero cells. The isolate UPM/2019-NS2 obtained from a goat was propagated in Lamb Testicular cells. It was used as a standard viral antigen for the indirect ELISA plates coating. Further information to evaluate possible risk factors was obtained by using a well-designed questionnaire. Based on the total samples tested, the overall seroprevalence for CE was found 71/341 (20.8%). However, only 45 (63.4%) of the seropositive samples were confirmed to have CE viral neutralizing antibodies as determined by using of SNT. The seroprevalence of CE in goat (24.5%) was significantly (p < 0.05) higher than in sheep (9.5%). There was a significant variation in the seroprevalence of CE among the five farms studied with farm D having the highest seroprevalence (30.9%) and the least was observed in farm C (8.3%). Sheep and goat kept in semi-intensive system of management showed significantly (P <0.05) higher seroprevalence than those in intensive system. Chi square test showed that variables: species, gender, age, farm, management system, vector control and proximity of farm to another livestock farm played a significant role in the prevalence of CE. Multivariate logistic regression analysis revealed that species and management system of the livestock farms have a significant influence on the presence of antibody against CE. Goats and animals kept under semi intensive management system were found to be 3.085 and 3.377 times more likely to be infected with CE disease as compared to sheep and those animals under intensive management respectively. Only five (5) out of six (6) scab samples were positive to CE virus as tested by PCR for B2L and F1L genes. All the positive samples were processed for Sanger sequencing and results obtained were blasted against NCBI GenBank database. Phylogenetic analysis of these DNA sequences revealed that CE virus isolates were closely related with orf virus UY15/09 from Uruguay, and also clustered together with orf virus TVCC/Shuhama, orf virus OV- 1A82 and orf virus SJ1 from India, USA and China respectively. The isolates were also closely related with previous orf virus isolates obtained from different regions in Malaysia. The percentage of similarity for B2L and F1L gene with other global isolates were used for evolutionary assessment within the range of 98-99% and 97- 99% respectively. This study revealed the current seroprevalence and possible risk factors associated with CE in sheep and goats in Negeri Sembilan, Malaysia. Seroprevalence of CE was high in goats compared to sheep. More breeds should be investigated because the antibody level could be differ among breeds. Prophylactic measures should be advocated to farmers by the authorities concerned for effective prevention and control measures.